Effect of freeze-thaw cycles on triaxial strength properties of fiber-reinforced clayey soil - Orakoğlu, Müge Elif; Liu, Jiankun (My University, 2017)
Understanding effect of freezing phenomenon in a fiber-reinforced soil structure is essential to foundation technology, road construction and earthwork application in cold region. This research aims to present the results of experimental investigation relative to the unconsolidated-undrained triaxial compression behavior of fine-grained soil as a function of freeze-thaw cycles and fiber volume fractions. All measurements were carried out for 3 selected glass and basalt fiber fractions (0%, 0.5%, and 1%) and 5 selected freeze-thaw cycles (0, 2, 5, 10, and 15). It has been observed that for the studied soil, strength of unreinforced soil reduced with increasing number of the freeze-thaw cycles while fiber-reinforced soil shows greater effect and the strength reduction amount reduces from 40% to 18%. Moreover, the reduction trend for cohesion of the fiber-reinforced soil decreased, this was seen more prevalent on 1% glass fiber-reinforced soil. The resilient modulus of all specimens reduced with increasing number of the freezethaw cycles. The experimental results demonstrated that different fiber fractions and their mixtures could be employed as supplement additive to improve the freeze-thaw performance of cohesive soils for road construction and earthworks.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Freeze-thaw cycles; Fiber-reinforced soil; Failure strength; Resilient modulus; Cohesive force; Friction angle